Susceptible Plasmonic Photonic Crystal Fiber Sensor with Elliptical Air Holes and External-Flat Gold-Coated Surface - Chung-Ting Chou Chao; Muhammad Raziq Rahimi Kooh; Yuan-Fong Chou Chau; Roshan Thotagamuge (Photonics, 2022)
This paper proposes and analyzes a simple surface plasmon resonance (SPR)-based elliptical air hole photonic crystal fiber (PCF) sensor. The fiber structure comprises an analyte channel of the fiber surface coated with a gold layer on the flat surface and the fiber’s external surface. Numerical simulations are conducted using the finite element method (FEM) with an external sensing approach. We found that the thickness of plasmonic material (Au) is the most crucial factor that affects the full width at half maximum (FWHM) and confinement loss amplitude. We also demonstrated that the proposed elliptical air hole SPR-PCF is superior to circular air hole SPR-PCF in terms of confinement loss and FWHM. According to the wavelength interrogation technique, the simulation results show that the designed SPR-PCF sensor can attain a maximum sensitivity of 116,500 nm/RIU and a resolution of 8.58 × 10−7 RIU (RIU: refractive index unit) for the analyte RI of 1.395. We believe the proposed SPR-PCF sensor can be a potential candidate for biomolecular and biological analyte detection.